A Redox Couple Strategy Enables Long‐Cycling Li‐ and Mn‐Rich Layered Oxide Cathodes by Suppressing Oxygen Release. Issue 14 (24th February 2022) - Shao, Qinong; Gao, Panyu; Yan, Chenhui; Gao, Mingxi; Du, Wubin; Chen, Jian; Yang, Yaxiong; Gan, Jiantuo; Wu, Zhijun; Zhang, Chenyang; Chen, Gairong; Zheng, Xusheng; et al.
Abstract: Li‐ and Mn‐rich layered oxides (LMROs) are considered the most promising cathode candidates for next‐generation high‐energy lithium‐ion batteries. The poor cycling stability and fast voltage fading resulting from oxygen release during charging, however, severely hinders their practical application. Herein, a strategy of introducing an additional redox couple is proposed to eliminate the persistent problem of oxygen release. As a proof of concept, the cycling stability of Li1.2 Ni0.13 Co0.13 Mn0.54 O2, which is a typical LMRO cathode, is substantially enhanced with the help of the S 2− /SO3 2− redox couple, and the capacity shows no decay with a retention of 100% after 700 cycles at 1C, far superior to the bare counterpart (61.7%). The surface peroxide ions (O2 2− ) are readily chemically reduced back to immobile O 2− by S 2− during charging, accompanied by the formation of SO3 2−, which plays a critical role in stabilizing the oxygen lattice and eventually inhibiting the release of oxygen. More importantly, the S 2− ions are regenerated during the following discharging process and participate in the chemical redox reaction again. The findings shed light on a potential direction to tackle the poor cycling stability of high‐energy anion‐redox cathode materials for rechargeable metal‐ion batteries. Abstract : Oxygen release is the main reason for capacity decay of Li‐rich cathodes. A novel redox couple strategy is proposed here to fundamentally solve this problem. As a proof of concept, the S 2− /SO3 2− redox couple can significantly suppress oxygen release by chemically reducing surface O2 2− back into immobile O 2−, thereby achieving the long‐term cycling stability of Li‐rich cathodes.